PENGARUH FAKTOR DISPOSISIONAL DAN SITUASIONAL PADA PERILAKU KEWARGAAN ORGANISASIONAL: KASUS PADA INDUSTRI PERBANKAN DI INDONESIA - D. Wahyu Ariani (Journal of Indonesian Economy and Business (JIEB), 2008)
The goal of this research is to test the relationship model between motive, structural dimension, relational dimension, and cognitive dimension, as well as core self evaluation personality with organizational citizenship behavior. The research integrates the use of attribution theory, social exchange theory, core self evaluation theory, and two raters of organizational citizenship behavior. Eventhough organizational citizenship behavior is positively correlated with social capital, motive, and personality, the relationship of each factor is not the same strength. This is due to differences in job conditions, environment, task independency, and research setting. A survey was conducted by using questionnaires from previous research. The questionnaires were sent to 128 branches of the bank industry located in 16 major cities in Java. The sample consisted of 636 tellers and 129 head tellers. Validity tests and reliability tests were used to test the questionnaires contents. The Structural Equation Modeling (SEM) was used to test the relationship among the variables. The result proved that organizational motive and core self evaluation personality have the strongest effect on individual organizational citizenship behavior. The result also showed that self rating and supervisor rating differs significantly with respect to organizational citizenship behavior. Both are valid and have an equal effect on organizational citizenship behavior. A thorough discussion on the relationship among the variables as well as on self rating and supervisor rating are presented in this paper.